PENGARUH JENIS SUSU TERHADAP SINERESIS, WATER HOLDING CAPACITY, DAN VISKOSITAS KEFIR DENGAN STARTER KEFIR GRAIN - Berlianti, Desi; Sumarmono, Juni; Rahardjo, Agustinus Hantoro Djoko (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The study aims to determine the effect of the use of various types of milk on syneresis, water holding capacity and viscosity of kefir. Materials and methods. The materials used were 2 liters of fresh cow's milk, 2 liters of low fat milk, 2 liters of full fat milk, 2 liters of fresh goat's milk, 2 liters of mixed milk and kefir grains (2% per 1 liter of milk). (CRD) and data analysis using ANOVA which was carried out by further testing using the BNJ follow-up test. Completely Randomized Design consisting of 5 treatments and 4 replications, each replication using 500 ml of milk. Different treatments using milk using kefir grain starter included P1 (cow's milk). fresh), P2 (full fat commercial milk), P3 (low fat commercial milk), P4 (fresh goat's milk) and P5 (a mixture of fresh cow's milk and fresh goat's milk). Results. The results of the analysis of variance showed that there was a very significant effect (P<0, 01) on the value of syneresis, water holding capacity and viscosity of kefir. Conclusion. The average result of the research obtained that the syneresis of kefir ranged from 29,005-64,345%, WHC ranged from 36-89,45%, and viscosity ranged from 6 7.7-422.15 cP. It was concluded that kefir produced using various types of milk using a kefir grain starter resulted in different syneresis, water holding capacity and viscosity. Fullfat milk produces the best quality kefir and fresh cow's milk produces low quality kefir.